Assessing Child-to-Parent Violence With the Child-to-Parent Violence Questionnaire, Parents’ Version (CPV-Q-P): Factor Structure, Prevalence, and Reasons - Contreras, Lourdes; León, Samuel P.; Cano-Lozano, M. Carmen (Frontiers in Psychology, 2020)
Child-to-parent violence has dramatically risen in the last decade, becoming a concerning issue in many countries, so research on this issue has also increased. However, most of the studies on this topic have been conducted with samples of adolescents, and very few with samples of parents. In addition, the variety of assessment instruments does not reflect the elements of this type of violence. Thus, the purpose of the current study was to examine the factor structure, reliability, and validity of the Child-to-parent Violence Questionnaire, parents’ version, in a sample of Spanish parents of adolescents. Moreover, the prevalence rates of the different types of violence and the reasons for violence were also examined. A total of 1,012 Spanish parents of adolescents aged between 12 and 17 years old (55.1% mothers, 44.9% fathers) were assessed using the Child-to-parent Violence Questionnaire, parents’ version (CPV-Q-P). Data indicated a matrix of 4 factors with 14 items, capturing psychological violence, physical violence, financial violence, and control/domain over parents, with adequate psychometric properties. Reasons for child-to-parent violence were grouped into instrumental and reactive reasons. The more frequent type of violence was control and domain over parents, followed by psychological, financial and physical violence, with no significant differences between mothers and fathers. Otherwise, instrumental reasons were more frequent than reactive types, with no differences between mothers and fathers. The CPV-Q-P is a useful instrument to assess child-to-parent violence from the parents’ perspective both in professional and research settings.